Community‐based smoking cessation treatment for adults with high anxiety sensitivity: a randomized clinical trial. (13th June 2021) - Smits, Jasper A. J.; Zvolensky, Michael J.; Rosenfield, David; Brown, Richard A.; Otto, Michael W.; Dutcher, Christina D.; Papini, Santiago; Freeman, Slaton Z.; DiVita, Annabelle; Perrone, Alex; Garey, Lorra
Abstract: Background and Aims: People with anxiety disorders are more likely to smoke and less likely to succeed when they try to quit. Anxiety sensitivity may underlie both phenomena, such that people with high anxiety sensitivity react to interoceptive distress by avoidance. This study aimed to test the efficacy of an exercise program that induced interoceptive distress and thereby created tolerance to this distress in a safe environment. Design, Setting and Participants: Randomized clinical trial at four YMCA branches in Austin, Texas, USA. Participants [ n = 150; 130 (86.7%) white; 101 (67.3%) female; meanage = 38.6, standard deviation (SD)age = 10.4] were adult, daily smokers with high anxiety sensitivity motivated to quit smoking, who reported no regular moderate‐intensity exercise. Interventions: Participants were assigned a YMCA personal trainer who guided them through a 15‐week intervention aerobic exercise program. Participants assigned to the personalized intervention trained at 60–85% of their heart rate reserve (HRR), whereas participants assigned to the control intervention trained at 20–40% of their HRR. Participants in both groups received standard behavioral support and nicotine replacement therapy. Measurements: The primary outcome was biologically verified 7‐day point prevalence abstinence (PPA) at 6‐month follow‐up. Findings: Sixty‐one per cent of participants were available at the 6‐month follow‐up. PPA at 6 months was higher in the personalized intervention than the control intervention [27.6 versus 14.8%; odds ratio (OR) = 2.20, 95% confidence interval (CI) = 1.28, 3.80, P = 0.005], assuming missing at random. Anxiety sensitivity declined in both groups with no evidence that this differed between groups. Conclusions: An exercise program of high intensity increased abstinence from smoking in people with high anxiety sensitivity, but may not have done so by reducing anxiety sensitivity.